(untitled) (Context: Journal of Interdisciplinary Studies, 2022)
This paper deals with the Teacher Training School in Sarajevo, its beginnings and history, and the generations of pupils who passed through its halls between 1961 and 1965. The author’s aim is to draw attention to an educational institution of exceptional importance for Bosnia and Herzegovina and one that had a major impact on education and culture. The paper outlines the fundamental educational values that informed the school during the period in question and how they are now viewed by former students, some 50 years later. The sample for the study comprised students from the aforementioned generations at the Teacher Training School whom the author was able to contact and who were prepared to answer questions regarding the school and its role. The students pointed out both the major positive features of the school and certain weakness that went along with them. From their answers, it is evident that the school had a significant positive impact on their development and left a profound and favourable impression on their memories. All of them emphasized that they would never forget their wonderful experiences at the school. They also rated very highly the qualities of their professors, whom they remember with pleasure and regularly invite to reunions. They still invite any able to join them. These generations’ views and opinions are a valuable contribution to a fuller understanding of this Bosnian and Herzegovinian educational institution, which served as alma mater for prominent teachers and intellectuals. This mini-research project involved the application of a survey research method, including interviews, questionnaires, and extrapolation. The survey was conducted with former students of the Sarajevo Teacher Training School present between 1961 and 1965.